AESTHETIC EXPERIENTAL TO VISITOR SATISFACTION AT THE GREEN VALLEY TOURIST PARK IN BANDAR LAMPUNG - Driya Wiryawan; Dwi Asri Siti A; Sherly Noveliza (Sean Institute, 2023)
An understanding of the Aesthetic Experiental is important to be used as a guide for the owners and managers of tourist attractions so as to provide an experience for visitors who visit the tourism park, for this reason the physical things that are in the environment of the Lembah Hijau Tourism Park have an important influence in providing the quality of services provided, so it is necessary to know visitor satisfaction based on the research of Lembah Hijau Tourism Park seen from the concept of Aesthetic Experiential. Therefore, the researcher is interested in conducting a study entitled